Different effects of focus in intra- and intersentential pronoun resolution in German. - Colonna, Saveria; Schimke, Sarah; Barbara Hemforth (Language, Cognition, and Neuroscience, 2015)
It is widely assumed that focused entities are more salient than non-focused ones and consequently, that an antecedent should be particularly available for a pronoun when it is foregrounded in a cleft construction. Contrary to this assumption, however, some studies observed that an antecedent focused by a cleft was less accessible than a non-focused one. We claim that the influence of clefting depends on the position of the ambiguous pronoun: clefted antecedents are only preferred as antecedents of a pronoun when the pronoun and its antecedent are in different discourse units. In order to test this hypothesis, we conducted a questionnaire and a visual world experiment in German in which we manipulated inter- vs. intra-sentential pronoun resolution. Results showed that clefting had different effects depending on the position of the pronoun. We will discuss why these results are consistent with the claim that pronouns preferentially co-refer with the sentence topic.
Keywords: eye-tracking; focus; information structure; language comprehension; pronoun resolution; visual world paradigm